Teacher Dispositions and Their Impact on Implementation Practices for the Gifted. Issue 4 (October 2019) - Stephens, Kristen R.
Teacher dispositions have become an important consideration in the preparation and evaluation of teachers. Often considered in combination with demonstrated knowledge and skills, educator preparation programs across the country have been tasked by accrediting bodies to both identify the essential dispositions required of licensed teachers and develop means for cultivating and assessing these dispositions. Dispositions often address a broad swath of areas and are assumed to be of uniform importance regardless of the teacher's grade level and content area; however, is it possible that certain dispositions are more essential for teachers of the gifted? Likewise, are there dispositions that have not been considered in our assessment of general education teachers that are critical for teachers of the gifted to possess? A thorough consideration of both these questions is necessary to ensure a cadre of teachers who are highly effective in working with gifted students.